Energy expenditure during an ultra-endurance cycling race - Francescato, M. P.; Di Prampero, P. E. (The Journal of Sports Medicine and Physical Fitness, 2002)
BACKGROUND: The energy expenditure of cycling has been investigated in great detail, mainly during trials performed for relatively short periods of time and under well established conditions. The number of investigations performed on long-lasting races, however, is very limited, probably because of practical difficulties. The aim of the present work was an attempt to estimate the energy requirements of 5 amateur cyclists who participated in an ultra-endurance long-lasting road cycling race. METHODS: A generalized equation obtained from literature was applied to calculate the energy expenditure of 26 to 137 short fractions of the competition. RESULTS: The calculated time weighted net metabolic power output ranged from 6.4 W x kg-1 to 10.8 W x kg-1; the corresponding net energy expenditure per unit distance ranging from 73.1 kJ x km-1 to 110.5 kJ x km-1. The total energy expenditure of the competition (rest included) ranged from 44.2 to 186.4 MJ, depending on the total competition duration. For all subjects, the sum total of the overall energy expenditure increased as a power function of cumulated performance time (kJ = 4872 x t0.77). However, the daily energy expenditure decreases with increasing the duration of the competition. CONCLUSIONS: It is concluded that it is possible to estimate the energy expenditure of ultra-endurance cycling performances, provided that the mechanical power output can be described by well defined equations.